The Risk of Skin Injury Caused by High-Rate Blunt Impacts to the Human Thorax - Shedd, D. F.; Berthelson, P. R.; Rifkin, J. A.; McMahon, J.; Giudice, J. S.; Forman, J. L.; Panzer, M. B. (Human factors and mechanical engineering for defense and safety, 2022)
Less-lethal weapons (LLWs) based on blunt impactors are seeing increased usage during crowd-control scenarios, and it is crucial that these devices do not inflict significant injuries when used. The guidelines for safe impactor design can be informed by rigorous biomechanical testing and injury risk analysis. In this study, high-rate blunt impact testing was conducted on five 50th percentile male post-mortem human surrogates to assess the tolerance of human skin to blunt impacts in situ. Six sectional-density matched cylindrical and spherical impactors ranging from 13 to 25 mm (0.5–1.0 in.) in diameter and 2.9–11.6 g in mass were used to impact four regions within the thorax at velocities ranging from 60 to 167 m/s. The free-flight impactor velocity was measured using high-speed video, and autopsies were performed to determine whether skin injury was induced at each impact site. Additionally, B-mode ultrasound imaging was employed to determine the tissue thickness at each impact location prior to test. Then, injury risk functions (IRFs) were developed to predict skin injury risk as a function of various test parameters. Regional anatomical differences were determined to have the greatest influence on the injury risk beyond velocity. Similarly, spherical impactors produced greater skin injury risk than the cylindrical impactors, and larger diameter impactors produced greater risk than smaller diameter impactors. The IRFs developed in this study will help guide future LLW design toward improved human safety and lower the risk of significant injury. Finally, this study will also help develop computational human body models capable of simulating skin injury response.